Acumulação de competências tecnológicas e suas implicações para o aprimoramento da performance técnico-econômica em operadoras e telecomunicações fixas: a experiência da Telemar Norte Leste S.A. - Bellinghini, Maria Fátima Fernandes (2003)
This dissertation examines the implications of the process of technological capability accumulation in the improvement of technical and economic performance of telecommunications company. This relationship was put under examination at Telemar Norte Leste, fixed services telephony operator, from 1998 to 2002. The application of tools based on descriptive structures to examine such implications is still scarce in the Brazilian scenario. The purpose of the current dissertation is to realize such an analysis, which is based on an individual case study supported by qualitative and quantitative empiric evidences that were achieved through interviews, direct observations and internai documentation study. For the examination of cumulative capability an existing descriptive structure was specifically adapted for fixed telephony. Accumulation of technological capability was studied in two dimensions: 'development of commercial processes, products and services' and development of telecommunications systems and operational processes'. Performance improvement was evaluated through the use of set of technical and economic indicators of representativity in the telecommunications arena. From the analysis carried on at Telemar, it follows that during the evaluation period, the company developed efforts in innovative competences that made possible the achievement of Levei 5, according to the analytical structure adapted for this dissertation. Evidences were found showing that the expertise accumulation had absolutely influenced the improvement of the twenty-nine indicators that were put under analysis. These evidences, once related with recent studies made at companies located at development countries, suggest that the accumulation of such expertise is determinant to adapt, modify or develop new technologies, being itself essential for the competitive company positioning and placing fundamental role to accomplish better results as shown by company performance indicators. There are other internai and externai factors that could also be considered as relevant in the evaluation of company competitiveness and to influence the results of corporate performance. This dissertation include comments on the global telecommunications crisis, caused by the drastic new economy investments reversal, that, since 2001 has been in the scenario bringing results that reflects planning revisions in the administration of the telecommunications companies. These factors and others, however, and taking into account the complexity of its implications, were not put under examination in the current study.